2010
DOI: 10.1136/gut.2009.185108
|View full text |Cite
|
Sign up to set email alerts
|

Gut CD103+ dendritic cells express indoleamine 2,3-dioxygenase which influences T regulatory/T effector cell balance and oral tolerance induction

Abstract: We identified a new IDO-dependent pathway leading to acquisition of tolerogenic functions in mucosal CD103-expressing DCs, indicating IDO as a possible therapeutic target for gut disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
264
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(286 citation statements)
references
References 42 publications
17
264
1
4
Order By: Relevance
“…Some studies have noted that colonic IDO appears to be expressed largely in the epithelium (10), whereas other studies indicated that IDO is mainly expressed in local dendritic cells in the intestinal lamina propria (6). In this study, we showed that Ido1 mRNA was expressed at similar levels in the colonic epithelial and interstitial tissues of untreated wild-type mice, supporting the earlier findings that colonic epithelium expresses IDO under physiological conditions (10).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies have noted that colonic IDO appears to be expressed largely in the epithelium (10), whereas other studies indicated that IDO is mainly expressed in local dendritic cells in the intestinal lamina propria (6). In this study, we showed that Ido1 mRNA was expressed at similar levels in the colonic epithelial and interstitial tissues of untreated wild-type mice, supporting the earlier findings that colonic epithelium expresses IDO under physiological conditions (10).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, recent studies have shown that increase of IDO concentrations in tissue inhibits migration of inflammatory cells, especially T cells (5). IDO is expressed in tissue macrophages and dendritic cells in a range of organs (6). Two types of IDO are known: IDO1 and the recently identified paralogue, IDO2 (7).…”
mentioning
confidence: 99%
“…S6 A-E). Expression of indoleamine 2, 3-dioxygenase (IDO) in several regulatory DCs inhibits T-cell responses (6,20). However, T-cell proliferation was not increased by addition of an IDO inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD103 + CX 3 CR1 − CD11b − DCs have been shown to generate and activate gut-tropic CD8 + T cells (16,17). These DCs have further been shown to induce development of Foxp3 + T reg cells (18)(19)(20). CX 3 CR1 + CD11b + DCs have been shown to mediate inflammatory responses through the induction of Th1 and Th17 cell development (15,(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…However, it is important to remember that the data concerning migratory CD103 + cells have been derived in mice and we do not know about the situation in humans. However, it has been shown that CD103 + CD11c + HLADR + cells derived from human colon express Indoleamine 2,3-dioxygenase, which in mice is involved in the ability of CD103 + DCs to drive Foxp3 + Treg cell development [36]. This suggests similarity between CD103 + DCs in mice and humans.…”
Section: Phagocyte Subsets In the Human Intestinementioning
confidence: 93%